'Prochainement: Arizona Jim contre Cagoulard': framing the future of the Front populaire in Jean Renoir's Le Crime de Monsieur Lange (1936). Issue 2 (3rd April 2018) - Nevin, Barry
Abstract: Gilles Deleuze remarks that Jean Renoir's entire œuvre displays the most fundamental operation of time, constantly holding the embodied past and the potential creation of a genuinely new future in tension. Although he fails to address Le Crime de Monsieur Lange, the film that cemented Renoir's association with the Front populaire, Deleuze tantalisingly remarks that this dialectic stems partly from Renoir's attitude towards the Front populaire. How Deleuze's framework allows spectators to interpret this film as an expression of Renoir's own ambivalence regarding the future of the Front populaire has yet to be sufficiently addressed. Drawing on Ida, an unfilmed screenplay written by Renoir during the making of Lange, this article argues that Renoir mobilises his signature techniques and proto-fascist iconography to reflexively criticise local attempts to implement socialist ideals in contemporary Paris.